Failure Analysis of Hydraulic Cylinder Bolt on Turntable Vibrating Compactor in Aluminum Processing Plant - Indah Permata Sari; Warman Fatra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The aluminum and its alloy have several characteristics i.e. relatively low density, high electrical and thermal conductivity and also good in corrosion resitance. The molding process of green anode blocks at an aluminum plant is carried out by an anode forming system. In this system, there is a printer called as turntable vibrating compactor or referred to as a ‘shaking machine’. During 55 seconds of anode block compaction, the fluctuating stress would be received by hydraulic cylinder bolt due to vibrations of the turntable vibrating compactor. Fluctuating stress that works continuously on the bolt can increase the tendency of failure. This paper aims to find out the causing factors and alternative solution for failure of the hydraulic cylinder bolt. To determine the cause of failure, several methods are carried out, i.e. fractography investigation, metallography examination according to ASTM E3-95, hardness testing according to ASTM E92-17 and tensile testing according to ASTM E8/E8M-16a. Fractography investigation show the failure mode of low cycle fatigue due to the application of high nominal stress. This is indicated by the presence of ratchet, beach mark, river mark and shear lip. The short life of the bolt due to the hardness and strength of the bolt after undergoing the heat treatment process Q + T cannot increase its endurance limit.